2021
DOI: 10.3390/su13094786
|View full text |Cite
|
Sign up to set email alerts
|

School Students’ Perception and Challenges towards Online Classes during COVID-19 Pandemic in India: An Econometric Analysis

Abstract: Due to the COVID-19 pandemic, the worldwide education system has been severely affected, following the shutdown of schools and colleges/universities since March 2020 in order to prevent the spread of the virus. Conventional classrooms shifted to online classrooms which profoundly impacted teachers’ and students’ closed interaction, making a paradigm shift in the teaching-learning process, inter alia. Against such a backdrop, it is relevant to analyze the perception of students and the challenges of online clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 17 publications
3
55
0
1
Order By: Relevance
“…A recent study on students' perception of the educational challenges induced by the COVID-19 pandemic [31] showed that learners prefer combined modes of instruction.…”
Section: Related Workmentioning
confidence: 99%
“…A recent study on students' perception of the educational challenges induced by the COVID-19 pandemic [31] showed that learners prefer combined modes of instruction.…”
Section: Related Workmentioning
confidence: 99%
“…The education sector has experienced significant evolution, shifting from a teacher- to learner-centered mode. As a result of the former, teachers play an important role as knowledge informants, while learners play a passive role as mere recipients of that knowledge [ 7 ]. However, within a learner-centered approach, learners are the producers of knowledge in the class under the guidance of the teacher.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the COVID-19 pandemic did not only lead to standstill global economic growth but also retroverted many countries' developmental progress (Statista, 2020). The worldwide education system is facing a new crisis due to the prolonged closure of schools and universities since March 2020 to curb the transmission of the disease and suddenly traditional classrooms have shifted into virtual classrooms having a staggering effect on the Indian educational sector because of the enormous digital divide (Khan et al, 2021). According to National Sample Survey Organisation (NSSO) 75th round report (2017)(2018), less than 15% of the rural households had Internet access compared to 42% of urban Indian households (NSSO, 2019) that not only leads to a wide rift in educational inequality but also exacerbates existing socio-economic disparities (Modi and Postaria, 2020).…”
Section: Introductionmentioning
confidence: 99%